“Won’t be enough to invite parents to school events”: Results of a systematic literature review of parental volunteering - Zsófia Kocsis; Valéria Markos; Elek Fazekas; Zsuzsanna Hajnalka Fényes; Gabriella Pusztai (Ricerche di Pedagogia e Didattica)
Investigating parental involvement has come to the focus of education studies in the past decade as research on family engagement has revealed its positive impact on children’s academic achievement. Parental volunteering at school may be an essential form of parental involvement, there is no evidence-based knowledge of its impact, nor has a systematic review been published on the subject yet. This paper reviews the literature on the relationship between parental volunteering and parental involvement through 29 studies published between 2004 and 2021. The studies apply a wide variety of research methodology and define parental volunteering either as an effective means of parental involvement or as an outcome of interventions and mentoring programmes. The results suggest that initiatives to involve parents become less common as educational level increases.